Distribution of conjunctive and disjunctive forms in Xitsonga - Lee, Seunghun J; Hlungwani, Crous (Stellenbosch Papers in Linguistics Plus, 2017)
The conjunctive and disjunctive forms in Xitsonga are examined with the purpose of presenting the distribution of these forms. While verbs in the conjunctive form are followed by some elements, the disjunctive is used when no element follows a verb. Xitsonga follows these basic patterns observed in other Bantu languages, but previous theories cannot explain all the occurrences of the distinction between the conjunctive/disjunctive forms. In previous work, three major approaches have been proposed: the constituency approach, the focus-based approach and the information packaging approach. Xitsonga shows support as well as counter evidence for all these approaches. This paper will also reexamine the claim that the presence of conjunctive/disjunctive distinctions only exists in the present tense. Following Creissels (2014), we report that the conjunctive/disjunctive dichotomy is present in other tenses as well when prosodic patterns such as penultimate lengthening are further examined.